2015
DOI: 10.4236/ajps.2015.615247
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Productivity and Fatty Acid Composition of Chlorella lobophora V M Andreyeva, a Potential Feed Stock for Biodiesel Production

Abstract: Green algae represent the fastest producible source of biomass that has diverse uses as biofuel, food, feed-stocks and the like. The biomass is rich in oils, which can be used as biofuel and the cultivation may be used to purify water as well. Productivity and quality of algal biomass depends on species and strains as well as environmental conditions of growth. Therefore, identification of new species and strains as well as standardization of media composition and environmental conditions for optimum yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…increased composition of C12:0, C14:0, C16:0, C16:1 and C18:3 while those of C18:0, C18:1 and C18:2 decreased compared to its oil counterpart. This was supported by the research of Kaur et al (2012), He et al (2013) and Santhoshkumar et al (2015). The FAME produced had 69.9% ester content.…”
Section: Algal Oil and The Derived Biodieselsupporting
confidence: 53%
“…increased composition of C12:0, C14:0, C16:0, C16:1 and C18:3 while those of C18:0, C18:1 and C18:2 decreased compared to its oil counterpart. This was supported by the research of Kaur et al (2012), He et al (2013) and Santhoshkumar et al (2015). The FAME produced had 69.9% ester content.…”
Section: Algal Oil and The Derived Biodieselsupporting
confidence: 53%
“…Champenois suggested that Coelastrella vacuolate is the current valid name for this C. pyrenoidosa [14]. Just a few studies are available on C. lobophora [26], [27], therefore, more research is required to assess the potential of C. lobophora for bioenergy production.…”
Section: Taxonomymentioning
confidence: 99%
“…1. Biomass productivity Biomass productivity, BP (kg.day -1 ) is estimated by the biomass accumulation using dry-weight measurement of algae culture as shown in the following equation (Santhoshkumar et al, 2015).…”
Section: Measurements and Determinationsmentioning
confidence: 99%